Design Of CO2 Removal System At Natural Gas Reserves - Norma Syahida binti Mazlan, Norma Syahida (Universiti Teknologi Petronas, 2010)
Natural gas is one of the principle sources of energy for many of our day-to-day needs and activities. It burns to form carbon dioxide (CO2) and water (H2O) without or with minimal smoke subject to composition. The presence of carbon dioxide in natural gas prior to combustion would lower the heating value of the gas, increase the volume of gas that must be transported and increase the environmental impact. Most of the existing acid gas treatment systems in gas plants are limited in CO2 removal capacity of 30 mol%. Hence this project aims to identify the feasible routes of the flowsheet for a CO2 capture system at offshore gas platforms to reduce the CO2 concentration in the raw natural gas from 20 – 90 mol% to 10 mol% before being sent to the acid gas treating plant in gas refineries using aminated resin. This feasibility of the CO2 removal system is investigated using simulation based approach in PETRONAS iCON software. The simulation is used to investigate the effect of mass fraction of aminated resin, lean aminated resin temperature and lean aminated resin circulation rate within the range of 0.25-0.55, 37-45°C and 3000-8000 m3/hr respectively on acid gas loading and percentage recovery of CO2. Based on the simulation results, it is predicted that the aminated resin has the potential to reduce CO2 from high CO2 loaded natural gas to meet the objective which is less than 10 mol% CO2 content. The best operating conditions are identified at mass fraction of 0.45, lean aminated resin temperature of 41°C and circulation rate of aminated resin of 7000m3/hr. A preliminary economic potential study shows that it is also economically viable.